2023
DOI: 10.1038/s41598-023-28641-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharmacogenetic variations on praziquantel plasma concentration and safety outcomes among school children in Rwanda

Abstract: School-based mass drug administration (MDA) of Praziquantel (PZQ) is the global intervention strategy for elimination of schistosomiasis. Genetic variations in drug metabolizing enzymes and transporter proteins influences drug exposure and treatment outcomes, but data on PZQ pharmacokinetics and safety outcomes are scarce. We investigated the effect of pharmacogenetics variations on PZQ plasma concentrations and safety outcomes among 462 Rwandan schoolchildren who received single dose PZQ and albendazole in MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The CYP2J2 *7 variant allele is reported to be associated with increased enzyme activity 34 , which is in line with our findings. A recent study reported the contribution of CYP2J2 genotype for PZQ metabolism though not statistically significant 31 . The significant association of CYP2J2 genotype with variability in PZQ plasma concentration in our study may indicate the contribution of CYP2J2 enzyme for PZQ metabolism.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The CYP2J2 *7 variant allele is reported to be associated with increased enzyme activity 34 , which is in line with our findings. A recent study reported the contribution of CYP2J2 genotype for PZQ metabolism though not statistically significant 31 . The significant association of CYP2J2 genotype with variability in PZQ plasma concentration in our study may indicate the contribution of CYP2J2 enzyme for PZQ metabolism.…”
Section: Discussionmentioning
confidence: 89%
“…The UPLC–MS/MS method of quantification of the analytes was done as described previously 20 , 31 . The calibration curves were constructed within the range of 2.4 to 2500 ng/mL for PZQ and cis -4-OH-PZQ, and from 24 to 25,000 ng/mL for trans -4-OH-PZQ, since the levels of trans- 4-OH-PZQ were very high in the samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in the PZQ treatment outcome between populations could be due to variability in infection intensity prevalence in different geo-locations, and the follow-up time in the study setting might contribute to the difference in ERR among pre-SAC infected with S. mansoni . Furthermore, recent studies highlight the importance of genetic variation for PZQ disposition [ 19 , 40 ], but the impact of genetic variations on PZQ treatment outcomes needs further investigation. Despite the relatively lower CR of pre-SAC with moderate-to-heavy intensity infection groups than the light-intensity infection, the moderate-to-heavy intensity showed satisfactory ERR.…”
Section: Discussionmentioning
confidence: 99%